Bio-lubricant production based on optimum epoxidized oleic acid using in situ peracid mechanism / Tunku Arif Zafri Tunku Ozir - Tunku Ozir, Tunku Arif Zafri (2022)
Conventional bio-lubricants are produced from petroleum, where petroleum-based components have the potential to give environmental threats. Bio-lubricants based on vegetable oil, such as palm oil, can be a replacement for petroleum as the base ingredient. The epoxidation process is essential to alter the vegetable oil into bio-lubricants. However, due to less study on the optimum process parameters, such as the molar ratio of formic acid (FA) to unsaturation dated palm oil oleic acid (OA), molar ratio of hydrogen peroxide (H2O2) to unsaturation dated palm oil oleic acid and the agitation speed, the optimum of each parameters was determined for the epoxidation of dated palm oil oleic acid by peracid in-situ peracid mechanism. The determination of the optimum process parameters used the one factor at a time (OFAT) method. The research was performed under a constant temperature of 60oC. Moreover, less research was found regarding the bio-lubricant productrion using epoxidized palm oil, thus, the second objective was to produce bio-lubricant from epoxidized oleic acid by the chosen method which was alcoholysis. The alcohols used consisted of methanol, tert-butyl alcohol and ethanolamine. The identity of the bio-lubricants were confirmed using Fourier Transform Infrared (FTIR) Analysis. Other than that, a kinetic modelling was performed using MATLAB, genetic algorithm optimization tool as a few reserch can be found to support the method. Apart from optimizing the epoxidation process, the reaction rates were determined. The optimum molar ratio of FA/OA, molar ratio of HP/OA and the agitation speed were obtained 1.0:1.0, 0.5:1.0 and 200 rpm respectively. Furthermore, the bio-lubricant produced by alcoholysis using three different alcohols were analyzed using Fourier-Transform Infrared Spectroscopy (FTIR). Lastly, the kinetic reaction rates were determined using genetic algorithm MATLAB optimization tool and the experimental data was compared together with the simulation data.